Exploring alexithymia with the French Perth alexithymia questionnaire: latent structure, profiles, and links with affective outcomes - Fantini-Hauwel, Carole; Gois, Cassandra; Luminet, Olivier; Banse, Emilie; Bigot, Alix; Noel, Xavier; Preece, David A. (Frontiers in Psychology, 2025)
IntroductionAlexithymia is of high clinical interest and its measurement remains an important evolving area of research. The Perth Alexithymia Questionnaire (PAQ) is a self-report measure designed to enable facet-level and valence-specific assessments of alexithymia. Here we aimed to introduce a French version of the PAQ, examine its psychometric performance, and use the PAQ to further explore the nature of the alexithymia construct.MethodParticipants in Belgium (N = 481) completed the PAQ and other self-report measures. Factor structure, reliability, and concurrent/discriminant validity were assessed, as well as an exploration of alexithymia profiles with latent profile analysis (LPA).ResultsConfirmatory factor analysis confirmed the PAQ had a theoretically congruent factor structure. All PAQ scores had high reliability and showed good concurrent validity with other measures of alexithymia, emotion regulation, and psychopathology. Sound discriminant validity was also established. Our LPA extracted eight profiles, highlighting the value of facet-level and valence-specific analysis of alexithymia. Some profiles had difficulties in all facets of alexithymia and both valence domains, whereas others had difficulties only in the appraisal of negative emotions.ConclusionOverall, our results indicate that the French PAQ has strong psychometric properties, and that facet-level and valence-specific assessments can be valuable in further understanding the alexithymia construct.